PERSPEKTIF NARATOLOGI TZVETAN TODOROV DALAM ADAPTASI FILM "THE FALLEN ANGEL" KARYA DAZAI OSAMU YANG DISUTRADARAI OLEH GENJIRO ARATO - Ananta, Benny Dele Bintang; Andini, Thathit Manon (EDUJ : English Education Journal, 2024)
Narratology, an interdisciplinary study of narrative texts, integrates literary studies, linguistics, philosophy, and psychology. It examines narrative structures, delivery, and reader interpretation. The film "The Fallen Angel," adapted from Dazai Osamu's novel "No Longer Human," exemplifies a literary work with a psychological narrative linked to human life. This study classifies the types of Todorov's five stages used in the film and assesses the implementation of these narrative structures from Tzvetan Todorov's perspective in "The Fallen Angel" by Genjiro Arato. This qualitative research employs narrative analysis using Tzvetan Todorov's narrative structure theory. Data are categorized into primary and secondary. Information is gathered through documentation and observation, with the author serving as a human instrument. The interactive analysis model guides the process, which includes information collection, reduction, presentation, and conclusion. The research shows that the plot idea consists of five stages: Equilibrium, Disruption, Recognition, Repair the Damage, and New Equilibrium. As well as the plot in Todorov's five-stage structure is then classified into a description of the form of results percent (17%) Equilibrium; (25%) Disruption; (33%) Recognition; (17%) Repair the damage; and (8%) New Equilibrium. This study carries important implications for film analysis, serving as a versatile tool for storytellers and educators, offering a deeper understanding of cinematic narrative construction, and demonstrating its broader applicability across various field